PEMBELAJARAN KJU!:ATIF-KJUTIS BERMUATAN HARD-SKILL DAN SOFT-SKILL MATA KULIAH ILMU PENDIDIKAN - Suryono, Yoyon (MAJALAH ILMIAH PEMBELAJARAN, 2007)
The purpose of the teaching through critical-creative learning model grant for educational science subject is to improve student ’s awareness of hard skill and . ·oft skill as two significant elemrnts of competencies that non formal education students must have. Tl.e grant results, which is a learning model to gain hard skill and soft skill a11d a critical-creative learning model, is appiicable for other subjects and even other study programs. Critical-creative learning model is able to develop student ’s mastery in hard skill and soft skill. The implementation of critical-creative learning model can be ref er to woup di.:;sion approach, concept understandir.g assignments, and problem solving assignments either individually or in groups. Howevu, further elaboration of hard skill and soft skill competency and critical-creative learning model must always be done through other subject using different model, strategy, method ·and approach.